Cytotoxicity of tumor antigen specific human T cells is unimpaired by arginine depletion - Munder, Markus; Engelhardt, Melanie; Knies, Diana; Medenhoff, Sergej; Wabnitz, Guido H.; Luckner-Minden, Claudia; Feldmeyer, Nadja; Voss, Ralf-Holger; Kropf, Pascale; Müller, Ingrid; Conradi, Roland; Samstag, Yvonne; et al. (PLOS ONE, 2013)
Tumor-growth is often associated with the expansion of myeloid derived suppressor cells that lead to local or systemic arginine depletion via the enzyme arginase. It is generally assumed that this arginine deficiency induces a global shut-down of T cell activation with ensuing tumor immune escape. While the impact of arginine depletion on polyclonal T cell proliferation and cytokine secretion is well documented, its influence on chemotaxis, cytotoxicity and antigen specific activation of human T cells has not been demonstrated so far. We show here that chemotaxis and early calcium signaling of human T cells are unimpaired in the absence of arginine. We then analyzed CD8(+) T cell activation in a tumor peptide as well as a viral peptide antigen specific system: (i) CD8(+) T cells with specificity against the MART-1aa26-35*A27L tumor antigen expanded with in vitro generated dendritic cells, and (ii) clonal CMV pp65aa495-503 specific T cells and T cells retrovirally transduced with a CMV pp65aa495-503 specific T cell receptor were analyzed. Our data demonstrate that human CD8(+) T cell antigen specific cytotoxicity and perforin secretion are completely preserved in the absence of arginine, while antigen specific proliferation as well as IFN-γ and granzyme B secretion are severely compromised. These novel results highlight the complexity of antigen specific T cell activation and demonstrate that human T cells can preserve important activation-induced effector functions in the context of arginine deficiency.
Gesehen am 25.06.2021